The therapeutic prospects of N-acetylgalactosamine-siRNA conjugates - Zhang, Lei; Liang, Yayu; Liang, Guohui; Tian, Zhili; Zhang, Yue; Liu, Zhihui; Ji, Xinying (Frontiers in Pharmacology, 2022)
RNA interference has become increasingly used for genetic therapy following the rapid develop-ment of oligonucleotide drugs. Significant progress has been made in its delivery system and implementation in the treatment of target organs. After a brief introduction of RNA interference technology and siRNA, the efficiency and stability of GalNAc-siRNA conjugates are highlighted since several oligonucleotide drugs of GalNAc have been approved for clinical use in recent years. The structure and features of GalNAc-siRNA conjugates are studied and the clinical efficiency and limitations of oligonucleotide-based drugs are summarized and investigated. Furthermore, another delivery system, lipid nanoparticles, that confer many advantages, is concluded, includ-ing stability and mass production, compared with GalNAc-siRNA conjugates. Importantly, developing new approaches for the use of oligonucleotide drugs brings hope to genetic therapy.